Impaired modulation of the cardiac L-type Ca2+ channel activity by ahnak-1 after myocardial infarction. - Alvarez González, Julio; Hasse, Hannelore; Vassort, Guy; Morano, Ingo (Revista Cubana de Cardiología y Cirugía Cardiovascular, 2012)
Introduction: The L-type cardiac Ca2+ channel (Cav 1.2) is an important determinant of cardiac repolarization and the main source of activator Ca2+ during excitation-contraction coupling in cardiac cells. Its defective regulation is a major cause of arrhythmias and contractile dysfunction. We have recently shown that the cytoskeletal protein ahnak-1 modulates Ca2+ current through Cav 1.2 channels (ICaL) by interacting with the regulatory beta-subunit of the Cav 1.2 channel and that the genetic variant of ahnak-1 I5483T (previously Ile5236Thr), interferes with the beta-adrenergic stimulation of ICaL. Objective: To extend our study of the I5483T variant to ventricular cardiomyocytes dissociated from remodelled infarcted rat hearts (PMI). Methods: The patch-clamp technique was used to record ICaL from enzymatically dissociated ventricular cardiomyocytes from young (2-month-old) and six-month-old sham-operated and PMI rats. Results: Basal ICaL was increased from 11 ± 0.5 A/F in young cardiomyocytes to 14.6 ± 1.1 A/F and 15.7 ± 1 A/F in sham and PMI cardiomyocytes respectively, while isoprenaline (ISO, 1 µmol/L) further increased ICaL by 101 ± 6%, 109 ± 10% and 104 ± 12% respectively. When cells were intracellularly perfused with a peptide containing the mutated ahnak-1 sequence (10 µmol/L) basal ICaL was increased to 20 ± 1 A/F, 22 ± 2 A/F and 21 ± 2 A/F in young, sham and PMI cardiomyocytes respectively. In these cells ISO increased ICaL by 11 ± 4%, 33 ± 6% and 79 ± 12% respectively. Conclusion: Modulation of ICaL by ahnak-1is impaired by myocardial ischemia and remodelling. Since ahnak-1 and Cav 1.2 channels co-localize in the transverse T-tubule system, remodelling of T-tubules could affect the interaction of ahnak-1 with the regulatory beta subunit of these channels. <!–[if gte mso 9]> Normal 0 <![endif]–>